Fast cure of stable semi-pregs via VBO cure - David B. Bender (Taylor & Francis Group, 2020)
To address the need for increased efficiency in high performance composite processing, a vacuum bag only (VBO) semi-preg was designed, modeled, and evaluated. The semi-preg featured a vinyl hybrid resin formulated for rapid cure. A model was developed to describe the kinetic behavior of the resin, and then was employed to guide the design of efficient cure cycles. The semi-preg featured a discontinuous distribution of resin on the fiber bed. The format imparted high through-thickness air permeability by virtue of the multitude of air evacuation pathways with short breath-out distances relative to conventional out-of-autoclave prepregs (OoA). The kinetic model was used to create a test matrix of panels from the semi-pregs. Microstructural quality, interlaminar shear strength, and glass transition temperature were compared to a control panel with a longer, conventional cure cycle. The results demonstrated that fast-cure resins can be used in conjunction with cure modeling and semi-preg formats to design appropriate VBO cure cycles that consistently yield parts with low defect contents without autoclaves.